Bioprinting techniques and risks for regenerative medicine - Mitchell, Maika G. (Elsevier/AP, Academic Press, and imprint of Elsevier, 2017)
Innovation is added value to a known process. Bioprinting: Techniques and Risks for Regenerative Medicine aims to stimulate a scientifically grounded, interdisciplinary, multiscale debate and exchange of ideas using the techniques described in the book. 3D printing and additive manufacturing evolved from within the field of Cell Biology will have the ability to recreate cells queried from large amounts of phenotypic and molecular data. Stem Cell biologists, biotechnologists and material engineers, as well as graduate students will greatly benefit from the practical knowledge and case examples provided throughout this book.--Provided by publisher.